Acinar cells modulate the tumor microenvironment through the promotion of M1 macrophage polarization via macrophage endocytosis in pancreatic cancer - Congjia Ma; Wenbo Zhu; Xiulin Hu; Deli Wu; Xintong Zhao; Yiqi Du; Xiangyu Kong (Discover Oncology)
Abstract Background Pancreatic ductal adenocarcinoma (PDA) is a highly aggressive and fatal cancer. M1 macrophages are generally considered to have anti-tumor properties, capable of suppressing tumor growth and metastasis by secreting pro-inflammatory cytokines and enhancing the immune response. Aims The objective of this research was to pinpoint crucial genes associated with M1 macrophages and search for a new way to activate the M1 phenotype of macrophages in PDA. Methods The level of immune cell infiltration was assessed using CIBERSORT in TCGA-PAAD cohort and ICGC-PACA cohort. We performed weighted gene co-expression network analysis (WGCNA) to identify the module most correlated with M1 macrophages and we identified hub genes through protein–protein interaction (PPI) analyse. Through survival analysis, correlation analysis and single cell analysis, we obtained the relationship between hub genes and prognosis, and the relationship between key genes and immune cells, as well as its expression in various cells. Results PRSS1 (Cationic trypsinogen) and CTRB1 (Chymosinogen B) were hub genes of the M1 macrophage-associated WGCNA module (211genes) and are closely related to the extension of survival time, which are also verified as cell growth-related genes by DepMap database. Through single-cell sequencing analysis, we determined that the expression levels of PRSS1 and CTRB1 in the acinar cells of tumor tissues were diminished. PRSS1 and CTRB1 are considered to be the signature genes of acinar cells. The proportion of acinar cells was also correlated with the infiltration of CD8T cells and M1 cells. Immunostaining revealed elevated expression levels of PRSS1 and CTRB1 in adjacent normal tissues. Cell line experiments confirmed that macrophages polarize towards M1 by engulfing pancreatic enzyme granules, thereby inhibiting the malignant phenotype of tumor cells. Conclusion Our findings highlight the critical role of acinar cells in modulating the immune microenvironment of pancreatic tumors by influencing macrophage polarization. This insight may provide novel opportunities for therapeutic interventions in cancer treatment.